2015
DOI: 10.1111/papt.12075
|View full text |Cite
|
Sign up to set email alerts
|

Attachment styles in patients with avoidant personality disorder compared with social phobia

Abstract: This is the first study to compare attachment styles in patients with avoidant personality disorder (AvPD) and social phobia (SP). The AvPD group had higher attachment-related anxiety than the SP group, and anxiety was most pronounced for the fear of abandonment. Fear of abandonment may play an important role in the AvPD pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 50 publications
1
21
0
2
Order By: Relevance
“…This evidence is consistent with the association between Mixed SP and depression [6]. A moderate correlation was found also between Automatic SP and Approval/Recognition Seeking EMS: individuals with more intense Automatic SP behaviour tend to put excessive emphasis on gaining approval from others, at the expense of developing a true sense of self, consistently with reports indicating approval seeking and Parameter set at 0 because redundant separation anxiety as predictors of avoidant personality [18]. This evidence might support the hypothesis that avoidant personality traits might be involved in the Automatic subtype, and that this subtype might be related to the so-called vulnerable narcissistic personality picture, often associated to avoidant personality, in the same manner as self-injurious behaviour [19].…”
Section: Predictive Effect Of Ems On Sp Subtypessupporting
confidence: 81%
“…This evidence is consistent with the association between Mixed SP and depression [6]. A moderate correlation was found also between Automatic SP and Approval/Recognition Seeking EMS: individuals with more intense Automatic SP behaviour tend to put excessive emphasis on gaining approval from others, at the expense of developing a true sense of self, consistently with reports indicating approval seeking and Parameter set at 0 because redundant separation anxiety as predictors of avoidant personality [18]. This evidence might support the hypothesis that avoidant personality traits might be involved in the Automatic subtype, and that this subtype might be related to the so-called vulnerable narcissistic personality picture, often associated to avoidant personality, in the same manner as self-injurious behaviour [19].…”
Section: Predictive Effect Of Ems On Sp Subtypessupporting
confidence: 81%
“… 72 In this study, DPD also showed some overlap with borderline PD on an attachment/abandonment factor. A fear of abandonment has also been identified in AVPD, 73 and two other studies reported significant correlations between AVPD and DPD symptoms, including unassertive behavior, low self-confidence with other people, and self-depreciation. 31 , 74 However, AVPD has been reported to differ from DPD by showing social withdrawal rather than proximity seeking 32 and by a stable association with alexithymia that in AVPD is independent of depression.…”
Section: Historical Development Of the Avpd Construct And Its Inclusimentioning
confidence: 90%
“…Similar developmental models have been proposed in relation to anxiety (Bifulco et al 2006;Warren, Huston, Egeland, & Sroufe, 1997), depression (Bifulco et al, 2006;Fowler, Allen, Oldham, & Frueh, 2013), bipolar disorder (Morriss, van der Gucht, Lancaster, & Bentall, 2009), posttraumatic stress disorder (Ortigo, Westen, Defife, & Bradley, 2013) and personality disorders (Ma, 2006), particularly the borderline (Choi-Kain, Fitzmaurice, Zarnarini, Laverdiere, & Gunderson, 2009;Fongay & Luyten, 2009) and avoidant (Eikenaes, Pedersen, & Wilberg, 2016;Hageman, Francis, Field, & Carr, 2015) types. Furthermore, the utility of attachment theory is demonstrated by a recent meta-analysis of 36 studies involving a total of 3,158 patients with a range of Axis I and Axis II diagnoses: Significantly better outcomes were observed for those with secure (as against insecure) attachment styles, on data collected across various psychotherapeutic orientations (Levy, Kivity, Johnson, & Gooch, 2018).…”
Section: Introductionmentioning
confidence: 60%